Systematic revision of the genera Geckobiella Hirst, 1917 and Hirstiella Berlese, 1920 (Acari: Prostigmata: Pterygosomatidae) with description of a new genus for American species parasites on geckos formerly placed in Hirstiella - Paredes-León, Ricardo; Klompen, Hans; Pérez, Tila M. (Zootaxa, 2012)
A cladistic analysis based on 274 morphological characters was performed including the 13 previously recognized speciesof the scale mite genus Hirstiella, 2 new species, 5 species in closely related genera, and 3 more distant out-group species.An analysis based on 148 informative characters resulted in one most parsimonious tree (L = 400, CI = 0.57 and RI =0.79). According to this, the genus Hirstiella in its current concept is a polyphyletic taxon whose member species belongto three different clades. The first lineage (Bremer support and jackknife values 2 and 78%) includes the type species H.trombidiiformis and seven additional species of Hirstiella that are parasites on iguanian lizards. The genus Geckobiella isincluded in this lineage, and the latter taxon name has priority over Hirstiella; therefore, the genus Hirstiella is considereda synonym of Geckobiella and no longer valid. For the second lineage (Bremer support and jackknife values of 2 and 73%)we propose the name Bertrandiella gen. nov.; it includes H. tenuipes, H. otophila, H. jimenezi and Bertrandiella chame-laensis sp. nov. The third lineage, and sister taxon of Bertrandiella, is a clade comprising Pimeliaphilus and the speciesH. sharifi and H. insignis. The latter taxa are transferred back to Pimeliaphilus (Bremer support and jackknife values >4and 100%). Updated diagnoses are provided for the genera Geckobiella sensu nov. (including a new species Geckobielladonnae sp. nov.) and Bertrandiella gen. nov., and for all their species, as well as for the genera Pimeliaphilus sensu nov.and Tequisistlana, based on the results of the phylogenetic analyses. The analyses support the hypothesis that lizards arethe ancestral hosts for Pterygosomatidae; associations with arthropods (in Pimeliaphilus) appear to be secondary, the result of host switching from lizards.